Mechanical and post-cracking characteristics of fiber reinforced concrete containing copper-coated steel and PVA fibers in 100 cement and fly ash concrete - Jalal, A. (MDPI AG, 2021)
This experimental study investigated the effects of polyvinyl alcohol (PVA) and copper-coated steel (CCS) on the mechanical properties and the post cracking behavior of fiber reinforced concrete (FRC). In designing high-performance concrete mixes, cement replacement materials are the essential ingredients. Therefore, the research objective was to investigate PVA and CCS fiberâs post-cracking performance in 100 cement concrete and concrete with 80 cement and 20 fly ash. The fiber content was fixed as a 0.3 volumetric fraction. CSS fibers required 15 more superplasticizer to achieve the desired slump of fresh concrete than the PVA fibers. Simultaneously, CCS fibers showed a 10 higher compressive strength than the concrete made of PVA fibers. Both fibers exhibited a similar effect in developing tensile and flexural strength. PVA fibers showed a value of 47 Gpa of secant modulus, and CCS fibers resulted in 37 Gpa in 100 cement concrete. In post-cracking behavior, CCS fibers showed better performance than the PVA fibers. The reason for this is that CCS showed 2.3 times the tensile strength of the PVA fibers. In comparing the two concretes, fly ash concrete showed about 10 higher compressive strength at 56 days and about 6 higher tensile and flexural strength. Similarly, fly ash concrete showed more than 15 first crack strength and flexural toughness than the 100 cement concrete in post-cracking behavior. Fiber-reinforced concrete containing PVA or CCS fibers showed enhanced post-cracking characteristics and its use could be preferred in structural applications. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.